Объяснение:
А)
0 * х = 0
0x = 0
0 = 0
х Є |R
Б)
9х - 3 = х + 5
9х - х = 5 + 3
8х = 8
х = 8 : 8
х = 1
В)
(х + 1)/4 + х/3 = (х - 3)/6 | * 12
3*(х + 1) + 4х = 2*(х - 3)
3х + 3 + 4х = 2х - 6
7х + 3 = 2х - 6
7х - 2х = -6 - 3
5х = -9
х = -9 : 5
х = -1,8
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
А)
0 * х = 0
0x = 0
0 = 0
х Є |R
Б)
9х - 3 = х + 5
9х - х = 5 + 3
8х = 8
х = 8 : 8
х = 1
В)
(х + 1)/4 + х/3 = (х - 3)/6 | * 12
3*(х + 1) + 4х = 2*(х - 3)
3х + 3 + 4х = 2х - 6
7х + 3 = 2х - 6
7х - 2х = -6 - 3
5х = -9
х = -9 : 5
х = -1,8